STUDENT MANAGEMENT IN THE DEVELOPMENT OF ACADEMIC AND NON-ACADEMIC ACHIEVEMENT IN THE ONE STUDENT ONE CERTIFICATE PROGRAM - Hadi Prasetyo (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Education is a process in which students explore and develop their potential through academic and non-academic fields. MA Superior Amanatul Ummah, Pacet Mojokerto International Standard Madrasa (MBI) program, an educational institution under the auspices of the Amanatul Ummah Islamic Boarding School foundation. The Institute has not a few academic and non-academic achievements every year and even always has very significant progress, especially in the achievements of national and international competition championships which always reach hundreds of achievements every year. This research resulted in a finding that Student Affairs has an active role in providing positive and productive activities through programs held by MBI students, namely One Student One Certificate, in other words, one student has one achievement, with coordination to all existing stakeholders and all kinds of service efforts. the guidance and escort given and based on regulations from Permendikbud number 5 of 2022 point 4 shows that there are many ways for high school level students to enter higher education through achievement pathways that have succeeded in leading students to qualify for the higher education they want.